2017
DOI: 10.1098/rspb.2017.1888
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in temperature-dependent phytoplankton traits revealed from a sediment archive: do reaction norms tell the whole story?

Abstract: The high evolutionary potential of phytoplankton species allows them to rapidly adapt to global warming. Adaptations may occur in temperature-dependent traits, such as growth rate, cell size and life cycle processes. Using resurrection experiments with resting stages from living sediment archives, it is possible to investigate whether adaptation occurred. For this study, we revived resting cysts of the spring bloom dinoflagellate from recent and 100-year-old sediment layers from the Gulf of Finland, and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Finally, although not a plant example, growth rates of phytoplankton show a strong threshold relationship with temperature (Fig. d), where growth rate drastically declines beyond a critical temperature (Hinners et al ., ).…”
Section: The Many Shapes Of Phenotypic Plasticitymentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, although not a plant example, growth rates of phytoplankton show a strong threshold relationship with temperature (Fig. d), where growth rate drastically declines beyond a critical temperature (Hinners et al ., ).…”
Section: The Many Shapes Of Phenotypic Plasticitymentioning
confidence: 97%
“…The GAM is a highly flexible model for complex reaction norm shapes (e.g. Hinners et al, 2017). Each population-level reaction norm shape is modelled along with three different scenarios of variation in the individual reaction norms, which are represented by different functions of each of the random effects separately (the three rows of Fig.…”
Section: Random Regression Mixed Model Frameworkmentioning
confidence: 99%
“…() found that after 1 year of experimental adaptation to elevated temperature (26.3°C), the marine coccolithophore Emiliania huxleyi evolved a higher population growth rate, smaller cell diameter and lower particulate organic and inorganic carbon content compared to cold (15°C)‐adapted populations. Hinners, Kremp, and Hense () found that 100‐year‐old resurrected strains of the marine dinoflagellate Apocalathium malmogiense did not differ in cell size or in its thermal reaction norm for growth compared to current strains, but that it did form resting cysts at a higher rate.…”
Section: Introductionmentioning
confidence: 99%
“…Although the difference is small, it is remarkably similar, both in character and degree, to latitudinal and altitudinal variation shown by other insect species over hundreds of kilometers (Bateman, 1967;Fujiyama and Harada, 1996;Liefting et al, 2009;Kutcherov et al, 2015), including the soil-dwelling springtail Folsomia candida (Stam et al, 1996). A taxonomically and conceptually distant but essentially similar example has recently come from phytoplankton studies: modern-day dinoflagellate strains, which experience seawater warming, show slightly faster growth rates, also at higher temperatures only, than strains revived from century-old sediments (Hinners et al, 2017). In all these cases, organisms from warmer thermal environments develop and/or grow slightly faster at higher temperatures relative to their colder-climate counterparts and reaction norms intersect around the lowest used experimental temperatures.…”
Section: Discussionmentioning
confidence: 57%